The Impact Of Certified Seeds Adoption On Cost Efficiency Of Horticultural Cultivation - Oktya Putri Gitaningtyas; Diah Widyawati (Journal of International Conference Proceedings, 2022)
This study aims to analyze empirically the impact of adoption of certified seeds on household cost efficiency of seasonal horticultural cultivation. This study uses dataÂ  from Cost Structure of Horticultural Cultivation Household SurveyÂ  (SOUH) 2018, Statictics Indonesia. The cost inefficiency variable is estimated using a one-step stochastic frontier. The results of the descriptive data show that labor costs are the biggest costs in the seasonal horticultural cultivation. On average, the proportion of households that adopt certified seed is still lower than households that do not adopt certified seed. In addition, the cost composition between adopters and non-adopters is different. The results of the stochastic frontier analysis show that the adoption of certified seeds has a positive effect on cost inefficiency, meaning that the adoption of certified seeds actually increases cost inefficiency/reduces cost efficiency. The impact of adopting certified seeds has not yet been felt by farmers because it has not lasted long.